Carbon and Nitrogen Mineralization of a Plant Residue Amended Soil: The Effect of Salinity Stress (Bangladesh Journal of Scientific and Industrial Research, 2012)
A factorial combination of saline and non-saline soil with three residue types (Sesbania grandiflora, Caliandra calothyrsus and Gliricidia maculata leaves) was used in laboratory incubation. The CO2-C content of plant residue amended soils was found to be increased steadily during the first two weeks of incubation followed by gradual reduction as incubation progressed. Under non-saline condition (EC=0.97 dS/m), the highest cumulative CO2-C content (1551 mg/kg soil) was observed in Caliandra amended soil, followed by Sesbania (1161 mg/kg soil) and Gliricidia (1042 mg/kg soil). The higher biodegradability of Caliandra leaves induced by the higher C content compared to the other residues. The CO2-C evolved under saline condition (EC=18.2 dS/m), ranged from 313 mg/kg (control) to 905 CO2-C mg/kg (Caliandra amended) soils. Sesbania amended non-saline soil showed the highest (227 mg/kg soil) and rapid release of NH4+-N, followed by Gliricidia (181 mg/kg soil) and Caliandra (177 mg/kg soil). Whereas under saline condition, release of NH4+-N ranged from 93 mg/kg (control) to 183 mg/kg (Sesbania amended). Though treatment behavior pattern of NO3--N was similar to that of NH4+-N throughout the incubation, saline soil showed significantly (P< 0.05) low NH4+-N and NO3--N contents compared to non-saline soil. Key words: Soil quality; Plant residues; Carbon and nitrogen mineralization; Salinity stress DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9608 BJSIR 2011; 46(4): 565-572